PROSES OPERASIONALISASI KEBIJAKAN KESATUAN PENGELOLAAN HUTAN: PERSPEKTIF TEORI DIFUSI INOVASI - Julijanti Julijanti; Bramasto Nugroho; Hariadi Kartodihardjo; Dodik Ridho Nurrochmat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
In forest management unit (FMU) operationalization, stakeholders are skeptical on the legitimacy of FMU policy, happening along their interaction. This interaction could encourage or inhibit the FMU policy adoption. This study goals is to analyze the FMU operationalization process and its influencing factors. Operationalization process is analyzed by analysis of qualitative descriptive based on stage of implementation and confirmation. Stakeholders interaction are analyzed by IDS method i.e. interaction between discourse/narrative, actors/networks and politics/interest. The results showed that FMU policy hasn't been fully recognized by stakeholders. Factors that affect the FMU policy operationalization are the clarity and adequacy of FMU authority, legitimacy of FMU policy and managements rights, the stakeholders support related to legality (regional policy) and action, and psychological barriers and trusts. Indicative strategies to overcome obstacles of the FMU operationalization are to establish and maintain the trust of stakeholders to support FMU operationalization bycommitment to a common goal in the FMU establishment, activity allocation suitable to the adopter needs, and participatory planning.